2016
DOI: 10.5194/isprsarchives-xli-b1-1093-2016
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest and Objected-Based Classification for Forest Pest Extraction From Uav Aerial Imagery

Abstract: Commission I, ICWG I/VbKEY WORDS: Superpixel, Simple Linear Iterative Cluster (SLIC), texture, Forest Pest, Random Forest, unmanned aerial vehicle (UAV) aerial imagery ABSTRACT:Forest pest is one of the most important factors affecting the health of forest. However, since it is difficult to figure out the pest areas and to predict the spreading ways just to partially control and exterminate it has not effective enough so far now. The infected areas by it have continuously spreaded out at present. Thus the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Unmanned aerial vehicle (UAV) imaging is a rapidly growing technology in recent years and has been widely applied in crop monitoring due to its high efficiency, high spatial and temporal resolution, low cost and easy customization [10]. Since 2010, high-throughput phenotyping by UAV imaging has been introduced to precision agriculture [11] in a range of applications, such as the detection of abiotic stress [12], nutrient deficiency [13] and biotic stress [14, 15], weed management [16], plant growth monitoring [1719] and yield prediction [20, 21]. In previous studies, low-altitude UAV equipped with a RGB camera was shown to be an effective method for counting rapeseed seedlings [22] and estimating canopy cover of cotton, sorghum and sugarcane [9, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Unmanned aerial vehicle (UAV) imaging is a rapidly growing technology in recent years and has been widely applied in crop monitoring due to its high efficiency, high spatial and temporal resolution, low cost and easy customization [10]. Since 2010, high-throughput phenotyping by UAV imaging has been introduced to precision agriculture [11] in a range of applications, such as the detection of abiotic stress [12], nutrient deficiency [13] and biotic stress [14, 15], weed management [16], plant growth monitoring [1719] and yield prediction [20, 21]. In previous studies, low-altitude UAV equipped with a RGB camera was shown to be an effective method for counting rapeseed seedlings [22] and estimating canopy cover of cotton, sorghum and sugarcane [9, 23].…”
Section: Introductionmentioning
confidence: 99%
“…The multiple decision trees of the RF are trained on a bootstrap sample of the original training data. At each node of every decision tree, one of a randomly selected subset of input parameters is chosen as the best split and used for node splitting [66]. Variable selection is significant for interpretation and prediction, especially for multidimensional datasets.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Various sensors can be mounted on UAVs, such as thermal infrared cameras [11], hyperspectral cameras [12], and LiDAR [13]. UAVs have been used for forest biomass estimation [14], tree height measurement [15], pest and disease monitoring [16,17], disaster assessment [18][19][20], fire surveillance and prevention [21], etc. UAV remote sensing data have high image and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%